In vivo CRISPR/Cas9 targeting of fusion oncogenes for selective elimination of cancer cells - M. Martinez-Lage (Nature Portfolio, 2020)
Fusion oncogenes (FO) are common in cancers, but specific targeting of these chimeric genes are challenging. Here the authors report a CRISPR/Cas9 strategy that targets two intronic regions to disrupt the FOs in cancer cells and show that this approach reduces tumour growth and prolongs survival in animal models of cancer.